ANALISIS ZAKAT PRODUKTIF TERHADAP INDEKS KEMISKINAN, NILAI MATERIAL DAN SPIRITUAL PARA MUSTAHIK - Nono Hartono; Mohamad Anwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2018)
Abstract. The Analysis of Productive Zakat on Poverty Index, Material and Spiritual Value of Mustahik. This research intend to (1) analyze the changes of mustahik household income after receive assistance from productive zakah funds from Cirebon Zakat Center and (2) identify the characteristics of material and spiritual values of mustahik after obtaining assistance from productive zakah funds from the Cirebon Zakat Center based on the CIBEST model. This study uses a quantitative approach with data collection techniques in the form of observation, interviews and filling out questionnaires. The statistical test and data analysis used are paired data t test and CIBEST model. The results of the study showed that mustahik household income after receiving productive zakah funds experienced a significant change. Before the assistance of zakah, the average household income of mustahik are Rp. 1,110,563, and after getting zakah the average household income of mustahik rise to Rp. 1,653,000. This means that there is an increase in the average household income of mustahik by Rp. 542,437. Based on the CIBEST model, the material and spiritual value characteristics of mustahik after assistance productive zakah funds from Cirebon Zakat Center experienced a change. After the assistance, the number of mustahik households in the category of prosperous households (quadrant I) increased by 47.50 percent. Whereas, number of mustahik households that fall into the material poor category (quadrant II) decreased by 25.00 percent. Likewise, the number of mustahik households included in the category of spiritual poor (quadrant III) and absolute poverty (quadrant IV) fell by 54.55 percent and 90.91 percent respectively. Abstrak. Analisis Zakat Produktif Terhadap Indeks Kemiskinan, Nilai Material Dan Spiritual Para Mustahik. Penelitian ini bermaksud mengkaji perubahan pendapatan rumah tangga mustahik setelah mendapatkan bantuan dana zakat produktif dari Zakat Center Thoriqotul Jannah Cirebon dan mengidentifikasi karakteristik nilai material dan spiritual mustahik setelah mendapatkan bantuan dana zakat produktif dari Zakat Center Thoriqotul Jannah Cirebon berdasarkan model CIBEST. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik pengumpulan data berupa observasi, wawancara dan pengisian kuesioner. Adapun uji statistik dan analisis data yang digunakan adalah uji t data berpasangan dan model CIBEST. Hasil penelitian menujukkan bahwa pendapatan rumah tangga mustahik setelah mendapatkan bantuan dana zakat produktif mengalami perubahan yang signifikan. Sebelum adanya bantuan dana zakat, rata-rata pendapatan rumah tangga mustahik adalah Rp 1.110.563 dan setelah mendapatkan bantuan dana zakat rata-rata pendapatan rumah tangga mustahik naik menjadi Rp. 1.653.000. Artinya terjadi peningkatan rata-rata pendapatan rumah tangga mustahik sebesar Rp. 542.437. Berdasarkan model CIBEST, karakteristik nilai material dan spiritual mustahik setelah mendapatkan bantuan dana zakat produktif dari Zakat Center Thoriqotul Jannah Cirebon mengalami perubahan. Setelah adanya bantuan dana zakat, jumlah rumah tangga mustahik yang berada pada kategori rumah tangga sejahtera (kuadran I) mengalami peningkatan sebesar 47.50 persen. Sedangkan jumlah rumah tangga mustahik yang masuk kategori miskin material (kuadran II) menurun 25.00 persen. Begitupun jumlah rumah tangga mustahik yang masuk kategori miskin spiritual (kuadran III) dan miskin absolut (kuadran IV) masing-masing turun sebesar 54.55 persen dan 90.91 persen.